KONSEPTUAL DESING MODEL FLOWMAP UNIT FARMASI DENGAN MENGGUNAKAN HCI (Human Computer Interface) UMUM SEBAGAI PEMBELAJARAN - Salsalida, Shelynda; Mahardika, Deny; Q. J., dkk, Aulia Qoni’ah (DINAMIKA DOTCOM, 2019)
Registration of patients from ED / ER, inpatients and outpatients can then see the doctor in question. The doctor's prescription will be taken to the pharmacy unit, to get a medication that is in accordance with the doctor's advice. In the pharmaceutical unit the demand for drugs, the purchase of drugs, drug sales and availability of drugs is very important. Everything is recorded in great detail, so that the availability of drugs will continue to exist in the pharmaceutical unit. While the conclusions on the flowmap analysis chart above are the highest number in the Warehouse bar diagram with the number 2 while for start, patient, emergency room / emergency room, hospitalization, outpatient, doctor, prescription treatment, type of medicine, prescription drugs, free drugs, input Drugs, debt data collection, payments, purchase fractures, drug storage, new drugs, damaged drugs, pricing, storage, transactions, external, internal, COD, distribution, and distribution purposes totaling 1. Keywords : Analysis of Flowmap, Inpatients, COD, Pharmacy